Circulating carotenoids are associated with favorable lipid and fatty acid profiles in an older population at high cardiovascular risk - Marhuenda-Muñoz, María; Domínguez-López, Inés; Langohr, Klaus; Tresserra-Rimbau, Anna; Martínez González, Miguel Ángel; Salas-Salvadó, Jordi; Corella, Dolores; Zomeño, María Dolores; Martínez, J. Alfredo; Alonso-Gómez, Angel M.; Wärnberg, Julia; Vioque, Jesús; et al. (Frontiers in Nutrition, 2022)
Carotenoid intake has been reported to be associated with improved cardiovascular health, but there is little information on actual plasma concentrations of these compounds as biomarkers of cardiometabolic risk. The objective was to investigate the association between circulating plasma carotenoids and different cardiometabolic risk factors and the plasma fatty acid profile. This is a cross-sectional evaluation of baseline data conducted in a subcohort (106 women and 124 men) of an ongoing multi-factorial lifestyle trial for primary cardiovascular prevention. Plasma concentrations of carotenoids were quantified by liquid chromatography coupled to mass spectrometry. The associations between carotenoid concentrations and cardiometabolic risk factors were assessed using regression models adapted for interval-censored variables. Carotenoid concentrations were cross-sectionally inversely associated with serum triglyceride concentrations [-2.68 mg/dL (95% CI: -4.15, -1.22) and -5.09 mg/dL (95% CI: -7.33, -2.85), p-values = 0.0003 and <0.00001 in women and men, respectively], lower levels of plasma saturated fatty acids [-0.09 % (95% CI: -0.14, -0.03) and -0.15 % (95% CI: -0.23, -0.08), p-values = 0.001 and 0.0001 in women and men, respectively] and higher levels of plasma polyunsaturated fatty acids [(0.12 % (95% CI: -0.01, 0.25) and 0.39 % (95% CI: 0.19, 0.59), p-values = 0.065 and 0.0001 in women and men, respectively] in the whole population. Plasma carotenoid concentrations were also associated with higher plasma HDL-cholesterol in women [0.47 mg/dL (95% CI: 0.23, 0.72), p-value: 0.0002], and lower fasting plasma glucose in men [-1.35 mg/dL (95% CI: -2.12, -0.59), p-value: 0.001].